(untitled) (Eurasian Journal of Ecology, 2026)
Extreme ecosystems represent natural models for studying the mechanisms of microbial adaptation to a complex of abiotic stress factors, including elevated mineralization, thermal stress, pH fluctuations, radiation exposure, and limited nutrient availability. Kazakhstan is characterized by a wide diversity of such unique natural environments; however, the biodiversity of phototrophic microorganisms inhabiting these ecosystems remains insufficiently studied to date. Contemporary climate challenges and the demand for sustainable bioenergy solutions have increased interest in extremophilic phototrophic microorganisms demonstrating adaptation to harsh environmental conditions. The goal of the present study was to assess the biodiversity and taxonomic structure of microalgae and cyanobacteria isolated from extreme aquatic and soil ecosystems in various regions of Kazakhstan. To achieve this objective, field expeditions were conducted at designated monitoring sites, and microbiological methods were employed to isolate axenic cultures. As a result of the study, 171 species and subspecies of phototrophic microorganisms were identified in soil samples, and 14 species in aquatic ecosystems, predominantly belonging to the classes Chlorophyceae, Cyanophyceae, and Bacillariophyceae. Axenic cultures representing six genera Chlorella, Anabaena, Synechocystis, Coelastrum, Leptolyngbya, and Phormidium were successfully obtained. The identified taxa exhibited morphological and ecological plasticity, reflecting their adaptation to thermal, saline, highly mineralized, and radiation-active environmental conditions. The obtained results indicate a high adaptive potential of phototrophic microorganisms inhabiting extreme ecosystems and highlight their prospects for the development of sustainable biotechnological processes, including biomass and lipid production for biofuel generation. Keywords: extreme ecosystems, biodiversity, phototrophic microorganisms